Analisis Penurunan Jumlah Defect Dalam Proses Tire-Curing Dengan Penerapan Konsep Six Sigma - Burhan Primanintyo; M. Yani Syafei; Dina Luviyanti (JIE Scientific Journal on Research and Application of Industrial System, 2016)
In tire manufacturing process, amount of defects that occur in the tire company has a tendency to increase and above the target limits. In order to improve the quality of tire manufacture, an analysis to decrease the number of defects is conducted by using the Six Sigma concept. The repair process is done to reduce the defect types Under Cure. This is a defect with the highest number from the seven types of defects. The design DOE (Design of Experiment) is used to determine the optimum setting tires in the cooking process. Defect Under Cure is a type of defect that occurs due to imperfection of tire cooking process (curing) and cause the tire become immature. By doing improvements on the process based on optimum setting, the sigma value of the company is increased by 4.209 sigma which previously amounted to 3.902 sigma.